Effect of helicopter transport on neurological outcomes in a mouse model of embolic stroke with reperfusion: AIR‐MICE pilot study. (17th September 2015) - Leira, Enrique C.; Zaheer, Asgar; Schnell, Thomas; Torner, James C.; Olalde, Heena M.; Pieper, Andrew A.; Ortega‐Gutierrez, Santiago; Nagaraja, Nandakumar; Marks, Nancy L.; Adams, Harold P.
Abstract : Background: Patients often suffer a stroke at a significant distance from a center capable of delivering endovascular therapy, thus requiring rapid transport by helicopter emergency medical services while receiving a recombinant tissue plasminogen activator infusion that was initiated locally. But little is known about how a helicopter flight may impact the safety and efficacy of recombinant tissue plasminogen activator‐induced reperfusion and patient outcomes. Aim: To establish a new animal method to address with fidelity the safety and overall effect of helicopter emergency medical services during thrombolysis. Methods: Prospective randomized open blinded end‐point study of an actual helicopter flight exposure. Adult C57BL/6 male mice were treated with a 10 mg/kg recombinant tissue plasminogen activator infusion two‐hours after an embolic middle cerebral artery occlusion. Mice were randomized in pairs to simultaneously receive the infusion during a local helicopter flight or in a ground hangar. Results: Eighteen mice (nine pairs) were analyzed. The paired t ‐test analysis showed nonsignificant smaller infarction volumes in the helicopter‐assigned animals (mean pair difference 33 mm 3, P  = 0·33). The amount of hemorrhagic transformation between the helicopter and ground groups was 4·08 vs. 4·56 μl, respectively (paired t ‐test, P  = 0·45). Conclusions: This study shows that helicopter emergency medical services do not have an inherent adverse effect on outcome in a mouse model of ischemic stroke with reperfusion. These results endorse the safety of the practice of using helicopter emergency medical services in stroke patients. The observed potential synergistic effect of helicopter‐induced factors, such as vibration and changes in altitude, with reperfusion merits further exploration in animal experimental models and in stroke patients.